2016
DOI: 10.1002/joc.4838
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of cold season lake‐effect cloud bands for the North American Great Lakes

Abstract: Geostationary Operational Environmental Satellite (GOES) visible imagery was used to identify lake‐effect (LE) clouds in the North American Great Lakes region for the cold seasons (October–March) of 1997/1998 through 2013/2014 to provide a comprehensive climatological description of the seasonal and interannual variability of LE cloud bands. During the average cold season, at least 60% of days each month had LE clouds over some portion of the Great Lakes region and nearly 75% of all LE days had LE clouds prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
(127 reference statements)
1
18
0
Order By: Relevance
“…For example, the winter of 2013-14 was a big snow year for western New York State, including the Catskill Mountains to the east. It was also a year with a high number of LE snowstorms (Laird et al, 2017). Our inspection of NEXRAD radar data for that winter corroborated this.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…For example, the winter of 2013-14 was a big snow year for western New York State, including the Catskill Mountains to the east. It was also a year with a high number of LE snowstorms (Laird et al, 2017). Our inspection of NEXRAD radar data for that winter corroborated this.…”
Section: Resultssupporting
confidence: 75%
“…Use of satellite data to study LE snow in the Great Lakes has typically focused on studies of cloud cover (e.g., Ackerman et al, 2013;Laird et al, 2017). We employed a combination of data sources, including a time series of NOAA IMS 4km snow maps along with weather radar and precipitation maps.…”
Section: Discussionmentioning
confidence: 99%
“…MPH at low level rarely happens, except for Lake Baikal (Figure c, locates approximately at 108°E, 53°N), Bohai Bay (Figure d, 118°E, 33°N), and western parts of the Sea of Japan (Figure e, 128°E, 40°N). Clouds form above Lake Baikal may be associated with lake effects (e.g., Alcott et al, ; Laird et al, ). Conversely, there is no significant land‐ocean difference in low‐latitude regions (shown in Figures e and ).…”
Section: Resultsmentioning
confidence: 99%
“…Satellite (e.g., Kristovich & Steve, 1995; Laird et al, 2016) and radar‐based methods (e.g., Laird, Desrochers, & Payer, 2009) are valuable for identification of lake‐effect climatology, though the reduced temporal availability limits their efficacy for evaluating long‐term trends. Kristovich and Steve (1995) reported Lake Michigan lake‐effect clouds on 17% of November days during their study period, which is remarkably similar to the frequency of LE days herein, while Laird et al (2016) found a much greater frequency of lake‐effect cloud structures.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have evaluated trends in Great Lakes snowfall, the lake‐effect contribution to the trend (when assessed) has been typically inferred from the spatial distribution (e.g., Bard & Kristovich, 2012; Clark et al, 2018) or by proxy (such as oxygen isotope data utilized in Burnett et al (2003)). The daily, event‐level attribution used herein provides a direct estimate of the lake‐effect trend contribution, informed by the lake‐effect snowfall paradigm based on decades of case studies (e.g., Peace & Sykes, 1966), climatology (e.g., Braham Jr & Dungey, 1995; Laird et al, 2016), forecasting (e.g., Niziol, 1987), numerical simulations and morphology (e.g., Hjelmfelt, 1990; Laird, Kristovich, & Walsh, 2003; Lavoie, 1972), and field campaigns (e.g., Kristovich et al, 2000). Given the favourable environment and spatial patterns of snowfall within this canon of research, a reasonable estimation of scaled‐up monthly or seasonal lake‐effect snowfall contributions should be feasible given daily or event‐level environmental characteristics and snowfall distribution.…”
Section: Introductionmentioning
confidence: 99%